tan*2α=(1-cosα)/(1+sinα)*(1+cosα)/(1-sinα)=sin*2α/cos*2α=tan*2α 左边=右边 故原式成立
利用等式中的“1”证明:tanα*(1-sinα)/(1+cosα)=cotα*(1-cosα)/(1+sinα)
1个回答
相关问题
-
求证明三角函数等式啊 1.tanα+cosα/(1+sinα)=secα 2.cotα/(1-tanα)+tanα/(1
-
证明tanα(1-sinα)/(1+cosα)=(1/tanα)·(1-cosα)/(1+sinα)
-
证明下列恒等式(1)1/tanα+cotα=sinαcosα(2)tanα+cotα-2/tanα+cotα+2
-
求证!快 sin^2α/(1+cotα)+cos^2α/(1+tanα)=1-sinαcosα
-
证明:[1+sinα−cosα/1+sinα+cosα=tanα2].
-
利用三角函数定义证明(cosα-sinα+1)/(cosα+sinα+1)=(1-sinα)/cosα
-
1.tan α(cosα-sinα)+ sinα(sinα+tanα)\1+cosα
-
证明恒等式 (cosα+tanα)/[(cosα/sinα)+1/cosα]=sinα
-
1+tanα/1-tanα=3+2√2,求(sinα+cosα)2-1/cotα-sinαcosα的值
-
证明:sin(-α)sin(丌-α)-tan(-α)cot(α-丌)-2cos^2(-α)+1=sin^2α